2006
DOI: 10.2989/16085900609490367
|View full text |Cite
|
Sign up to set email alerts
|

Is khat-chewing associated with HIV risk behaviour? A community-based study from Ethiopia

Abstract: This study examines the possible association between the stimulant khat and risky sexual behaviour that might aggravate the spread of HIV. A community-based cross-sectional survey involving 4 000 individuals and focus group discussions were conducted to assess the attitudes and perceptions of an Ethiopian population towards the habit of khat-chewing and its possible association with risky sexual behaviour. All participants in the focus group discussions and 38% of the survey respondents were of the opinion tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In Ethiopia, khat has historically been used by Muslim males during prayer and more recently to alter mood, increase energy and improve work performance (Kebede et al, 2005; Gebissa, 2010b; Dawit et al, 2006). Currently, 15% of individuals aged 15 to 49 report using khat, though this number can be as high as 50% in some regions (Halle and Lakew, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ethiopia, khat has historically been used by Muslim males during prayer and more recently to alter mood, increase energy and improve work performance (Kebede et al, 2005; Gebissa, 2010b; Dawit et al, 2006). Currently, 15% of individuals aged 15 to 49 report using khat, though this number can be as high as 50% in some regions (Halle and Lakew, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using khat is also associated with elevated alcohol use (Dawit et al, 2006) and alcohol use disorders (Soboka et al, 2015). Khat users report that alcohol helps them manage side effects that are sometimes associated with khat use including insomnia, anxiety, and, for some men, impaired sexual performance or impotence despite the increased sexual desire associated with khat use (Dawit et al, 2006, Berhanu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol consumption increases sexual desire and arousal, although it lowers physiological arousal [6]. Effects of khat on the chewer include increased levels of energy, increased self-esteem, euphoria, increased libido, excitement, and increased proclivity for social interaction [7]. Cigarette smoking has been shown to reduce sexual arousal by impeding the circulatory system's delivery of oxygenated blood throughout the body [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, substance use among adolescents is a growing problem, as in many African countries. Several studies which were done in Ethiopian universities and High Schools among adolescents were evidences for this (Dawit et al, 2006;Lemma, 2009;Alem et al, 2010;Teferi, 2011;Reda et al, 2012;Gebreslassie et al, 2013;Kidane, 2014;Tadesse, 2014;Kassa and Deyno, 2014;Eticha and Kidane, 2014;Mossie et al, 2015;Tadesse et al, 2016). For instance, to indicate few, a study done on cigarette smoking among undergraduate students at Hawassa University revealed a lifetime prevalence that accounts for 14.8% and current prevalence of 7.5% (Kassa and Deyno, 2014).…”
Section: Introductionmentioning
confidence: 88%